H∞ optimal full information control for discrete time systems - Green, M; Limebeer, D (IEEE, 1990)
A representation formula is derived for all full-information controllers which satisfy an L∞ type constraint in the discrete time, time varying, finite horizon case. Unlike earlier work, focus is on the optimal case. The approach is based on the theory of linear quadratic difference games. Necessary and sufficient conditions for the existence of a solution as well as a linear fractional characterization of all solutions are the main results obtained.